2010
DOI: 10.1007/s00228-010-0938-7
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoetin as a novel agent with pleiotropic effects against acute lung injury

Abstract: Current pharmacotherapy for acute lung injury (ALI) and the acute respiratory distress syndrome (ARDS) is not optimal, while the biological and physiological complexity of these severe lung injury syndromes requires consideration of combined-agent treatments or agents with pleiotropic action. In this regard, exogenous erythropoietin (EPO) represents a possible candidate since a number of preclinical studies have revealed beneficial effects of EPO administration in various experimental models of ALI. Taken toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 86 publications
(167 reference statements)
0
24
0
Order By: Relevance
“…Accumulating evidence has indicated that erythropoietin exerts anti-apoptotic and tissue-protective effects in a variety of human diseases, such as myocardial infraction (1618), diabetes mellitus (19), spinal cord injury (2022), ischemia-reperfusion (I/R)-induced kidney injury (23) and acute lung injury (24,25). Galeano et al reported that recombinant human EPO (rhuEPO) may be an effective therapeutic approach for improving clinical outcomes by enhancing the wound content of vascular endothelial growth factor (VEGF) following thermal injury (26).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has indicated that erythropoietin exerts anti-apoptotic and tissue-protective effects in a variety of human diseases, such as myocardial infraction (1618), diabetes mellitus (19), spinal cord injury (2022), ischemia-reperfusion (I/R)-induced kidney injury (23) and acute lung injury (24,25). Galeano et al reported that recombinant human EPO (rhuEPO) may be an effective therapeutic approach for improving clinical outcomes by enhancing the wound content of vascular endothelial growth factor (VEGF) following thermal injury (26).…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoietin has long been reported for its pleiotropic effects against ALI/ARDS (11). Together with other researches, our previous articles focused on the protective effects of EPO on ALI, which also presented a significant improvement on lung tissue recovery.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies revealed that erythropoietin (EPO) played as a multifunctional endogenous mediator participating in various pathophysiological processes during critical illness (11). It is also reported as a stimulant for EPC proliferation and mobilization and may exert its protective effects on endothelial cells to maintain the integrity of pulmonary endothelium during ALI/ARDS (11Y13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined Epo as a protective agent in ischemia-reperfusion injuries of the heart and kidney 89 and in acute lung injury models. 90 …”
Section: Erythropoietinmentioning
confidence: 99%